Ways Of Determining The Competence Of Pedagogues And Calculating Factors Affecting It - Dilmonov Kudrat Bakhtiyorovich (Academia One Publishing, 2025)
the article considers ways to determine the potential of pedagogues and calculate the factors affecting it. In this way, the ways of determining the level of the potential of pedagogues, which is one direction of human potential, and the factors affecting its change, using the method of calculating the chain replacement method of economic analysis, the possibilities of making management decisions as a result of the calculation are revealed
Keywords: potential; human potential